Evaluasi Sistem dan Prosedur Penerbitan Surat Perintah Pencairan Dana pada Badan Keuangan Daerah Kabupaten Trenggalek - Prasetya, Mangkoe; Dyah Pravitasari (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Sulrat Pelrintah Disbursement of Funds (SP2D) is a certificate which is implemented to disburse funds through banks which is called seltellah Sulrat Pelintah Disbursement of Funds (SPM) is received by the Regional Ulmulm Sub-district Treasurer (BUlD), Sulrat Pelintah Disbursement of Funds (SP2D) in the form of the Unit Kelrja Pelrangkat District in Kabulpateln Trelnggalelk ulntulk disburses the funds that have been stipulated in the draft budget of each Regional Work Unit (SKPD) which are used for community welfare. The object of research is the Trelnggalelk District Regional Religious Agency. This research ultimately aims to evaluate the Systelm and Proceeds of Subdistrict Government Disbursement of Funds at the Regional Sub-district Agency of Trelnggalelk Kabulpateln. The analysis method used is qualitative by collecting data which is then processed and described. Research data can be obtained by interviewing related parties and processing documents related to research. The results of the research on the evaluation of the Sulrat Regional Government's Disbursement of Funds (SP2D) system and procedures for cash distribution on re-sales at the Regional Reliance Agency of Kabulpateln Regency, the transaction has been carried out in conjunction with the cash distribution accounting system as well as the existing regulations which include related functions, documents and documents. used, accounting records used and the cash distribution accounting system process network.